Aphid Transmission Alters the Genomic and Defective RNA Populations of Citrus tristeza virus Isolates - Albiach-Martí, María R.; Guerri, José; Hermoso-De-Mendoza, Alfonso; Laigret, F.; Ballester-Olmos, José F.; Moreno, Pedro (The American Phytopathological Society (APS), 2020)
A total of 14 Spanish isolates of Citrus tristeza virus (CTV) and 1 isolate from Japan were transmitted by Aphis gossypii, and the subisolates obtained were compared with the source isolates for symptom expression and double-stranded RNA (dsRNA) pattern. Of the 14 Spanish isolates, 9 showed altered dsRNA patterns after aphid transmission but only minor variations in the intensity of symptoms induced on Mexican lime. Northern blot hybridization with complementary DNA (cDNA) probes corresponding to both the 5¢ and the 3¢ termini of the CTV genomic RNA (gRNA) showed that the dsRNA bands that could be used to discriminate between the dsRNA pattern of the source and the aphid-transmitted isolates were the replicative forms of defective RNAs (D-RNAs). Conversely, the Japanese isolate and two subisolates obtained from it by aphid transmission had the same dsRNA pattern, but one of the subisolates induced milder symptoms in several hosts. Dot-blot hybridization with cDNA probes representing several regions of the gRNA showed that most of the aphidtransmitted isolates differed from the corresponding source isolate by their hybridization pattern. Our results indicate that aphid transmission often sorts the populations of gRNA variants and D-RNAs present in CTV isolates.